PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU SD MUHAMMADIYAH UNGGULAN DI KABUPATEN TEMANGGUNG - Rochiyanti, Ana (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
This study aims to find out how the leadership of the principal, how is work motivation, how is organizational commitment, is there an influence between leadership and teacher performance, is there an influence between work motivation and teacher performance, is there an effect between organizational commitment and teacher performance, and is there a joint influence between leadership, work motivation, and organizational commitment on the performance of SD Muhammadiyah Unggulan teachers in Temanggung Regency. This research is a quantitative research with data collection techniques through questionnaires. Validity test using normality test and linearity test.The results showed: 1) the principal's leadership was in good criteria, namely 67.5%, 2) work motivation was in the good category at 52.5%, 3) organizational commitment in the good category was 52.5%, 4) teacher performance in good category by 50%, 5) there is a positive and significant influence between leadership and teacher performance of 7.93%, 6) there is a positive and significant influence between work motivation and teacher performance of 47.0%, 7) there is a positive and significant influence between organizational commitment and teacher performance of 6 ,09%, 8) there is a positive and significant influence between leadership, work motivation, organizational commitment to teacher performance of 65.3%.